Overproduction and easy recovery of target gene products from cyanobacteria, photosynthesizing microorganisms - Asayama, Munehiko (Springer-Verlag, 2012)
New cyanobacterial expression vectors, possessing an origin of replication that functions in a broad range of Gram-negative bacteria, were constructed. To inspect the shuttle vectors, the gene gfp was cloned downstream from the expression control element (ECE) originating from the regulatory region of the Microcystis aeruginosa gene psbA2 (for photosystem II D1 protein), and the vectors were introduced into three kinds of cyanobacteria (Synechocystis sp. PCC 6803, Synechococcus elongatus PCC 7942, and Limnothrix/Pseudanabaena sp. ABRG5-3) by conjugation. Multiple copy numbers of the expression vectors (in the range of 14–25 copies per cell) and a high expression of green fluorescent protein (GFP) at the RNA/protein level were observed in the cyanobacterial transconjugants. Importantly, GFP was observed in a supernatant from the autolysed transconjugants of ABRG5-3 and easily collected from the supernatant without centrifugation and/or further cell lysis. These results indicate the vectors together with the recombinant cells to be useful for overproducing and recovering target gene products from cyanobacteria. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00253-012-3989-0) contains supplementary material, which is available to authorized users.